Large vessel calcification in Takayasu arteritis. Issue 5 (14th May 2013) - Gujadhur, A.; Smith, E. R.; McMahon, L. P.; Spanger, M.; Chuen, J.; Holt, S. G.
Abstract We report the novel case of a young woman with Takayasu arteritis, with extensive large vessel disease. The case demonstrates that while mechanisms of vascular calcification are poorly understood, inflammation per se might be sufficient to mediate increased mineral stress leading to vessel calcification, even in the absence of renal impairment.